ANALISIS PERMINTAAN ANGGUR IMPOR DI KABUPATEN ACEH BARAT - Fariz Rizki Thamrin; Nur Aidar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThe purpose of this research is to analyse the demand for imported wines in West Aceh district. The type of data used is primary and secondary data. The population studied were residents of the district of Johan Pahlawan and samples were taken from Gampong Ujong Baroh, Rundeng and Seuneubok. The data analysis method used is a double linear regression method. The results showed that the prices of imported wines, revenues, and local wine prices were partially positively influential to the demand for imported grapes. The magnitude figure of the coefficient of adjusted determination (R2) is 0.686 meaning that the influence of the third free variable to the imported wine demand is 68.6 percent, while 31.4 percent is influenced by other variables outside the model. Government is able to issue a price policy that is easily reachable by all circles, and the efforts that the fruit traders can make to increase the purchase of imported grapes is to provide an affordable price so as to provide More benefits for the buyer.Keywords: Imported Wine Prices, Consumer Revenues, Local Wine Prices, Imported Wine Demand